2020
DOI: 10.3390/nano10030440
|View full text |Cite
|
Sign up to set email alerts
|

Electro-Optical Properties of Monolayer and Bilayer Pentagonal BN: First Principles Study

Abstract: Two-dimensional hexagonal boron nitride (hBN) is an insulator with polar covalent B-N bonds. Monolayer and bilayer pentagonal BN emerge as an optoelectronic material, which can be used in photo-based devices such as photodetectors and photocatalysis. Herein, we implement spin polarized electron density calculations to extract electronic/optical properties of mono- and bilayer pentagonal BN structures, labeled as B 2 N 4 , B 3 N 3 , and B 4 N 2 . Unlike the insulating hBN, the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 52 publications
1
12
0
Order By: Relevance
“…These results agrees well with the earlier reported results. 14,15,43 Observation of band structure diagram and DOS plot revealed that the B-2p states populated the conduction band and N-2p states populated the valence band, respectively. Electron density distribution plot in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These results agrees well with the earlier reported results. 14,15,43 Observation of band structure diagram and DOS plot revealed that the B-2p states populated the conduction band and N-2p states populated the valence band, respectively. Electron density distribution plot in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…11 h-BN bilayer has been studied for its potential application in thermoelectric devices due to its superior thermal conductivity 12 and for nano-electronic, opto-electronic devices by modulating the energy band gap by applying external electric field, strain, doping etc.,. [13][14][15][16][17] Extensive research on h-BN mono-layer, graphitic carbon nitride, boron carbide mono-layer's potentiality reversible hydrogen storage system for mobile applications are in progress. [18][19][20][21][22][23][24][25] Panigrahi et al, reported co-adsorption innovative technique for hydrogen storage of lithiated carbon nitride (C 7 N 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…The adsorption/desorption kinetics and the strength of binding energy ought to be intermediate for hydrogen to bind on the material surfaces with an optimal adsorption energy range. Owing to the obvious reasons mentioned above and the survey of previous works, 2D bilayer h -BN looks promising with numerous adequate functional properties such as high mechanical stability, carrier mobility, and outstanding electronic and optical properties which encourages its further utilization for energy-storage applications. Motivated by this, we explore the possibility of using bilayer h -BN for H 2 storage by employing first-principles calculations. We analyzed trends in binding energy, desorption temperature, effective mass of electron and holes, and subsequently their effects on the structural and electronic properties of bilayer h -BN using state-of-the-art computational techniques.…”
Section: Introductionmentioning
confidence: 99%
“…Carbon exists widely in nature and can form allotropes [ 1–15 ] in various hybrid ways. As an isoelectronic of carbon, boron nitride also has many polymorphs, [ 16–38 ] it also contains some 2D structures, [ 27,29,32,37 ] we know that 2D materials may have higher electron mobility or hole mobility, which has the advantages that 3D materials do not have. c‐BN as a wide bandgap semiconductor material, with high breakdown electric field, high thermal conductivity, high mobility, high resistivity, low dielectric constant, can realize double doping, and has good stability.…”
Section: Introductionmentioning
confidence: 99%